Anti-idiotype antibodies and phage displayed peptides as antigenic mimics of a Mycoplasma capricolum subsp. capripneumoniae epitope - Nel, Louis Hendrik (University of Pretoria, 2013)
Dissertation (MSc (Microbiology))--University of Pretoria, 2007.